Evaluación del contenido de metales pesados en lodos residuales aerobios. - García, Hendrina; El Zauahre, Maziad; Acosta, Yudith; Morán, Héctor; Toyo, Ligia; Fernández, Nola (Multiciencias, 1970)
Ver resumen pdf.